Relationship between Age and Nutritional Status and Length of Stay of Typhoid Fever Patients at Dr. Soehadi Prijonegoro General Hospital, Sragen, Indonesia - Nurhayani; Rizky Hari Fernanda (HM Publisher, 2023)
Typhoid fever is one of the cases of infection that still tends to be high in Indonesia. There is a role for IgG antibodies in the clinical condition of typhoid fever patients. The immune status of an individual is largely determined by nutritional status and age. This study aimed to determine the relationship between age and nutritional status and length of stay of typhoid fever patients at Dr. Soehadi Prijonegoro General Hospital, Sragen, Indonesia. This study was an analytic observational study with a cross-sectional approach. A total of 106 subjects participated in this study. Univariate and bivariate analyses were performed on this study data using SPSS. There is a relationship between age and length of stay, where age over and/or equal to 30 years is at risk of getting longer care than patients who are less than 30 years old. This study also shows that there is no relationship between nutritional status and length of stay of typhoid fever patients.